Sectorgap: An R package for consistent economic trend cycle decomposition - Sina Streicher (ETH Zurich, KOF Swiss Economic Institute, 2024)
Determining potential output and the output gap-two inherently unobservable variables-is a major challenge for macroeconomists. This paper presents the R package sectorgap, which features a flexible modeling and estimation framework for a multivariate Bayesian state space model identifying economic output fluctuations consistent with subsectors of the economy. The proposed model is able to capture various correlations between output and a set of aggregate as well as subsector indicators. Estimation of the latent states and parameters is achieved using a simple Gibbs sampling procedure and various plotting options facilitate the assessment of the results. An illustrative example with Swiss data outline data preparation, model definition, estimation, and evaluation using sectorgap.
Keywords: 330; R; state space models; time series; simulation smoother; Gibbs sampling; business cycle; output gap; potential output